Peranan Produk dan Promosi dalam Meningkatkan Minat Kunjungan ke Jakarta Aquarium & Safari - Yustisia Kristiana; Louisa Patricia; Vina Dewi Tanjung (Journal of Event, Travel and Tour Management, 2022)
Jakarta Aquarium & Safari is one of the tourist attractions in Jakarta that has experienced a decline in visits due to the COVID-19 pandemic that has been going on since 2020. To suppress the spread of this virus, social restrictions have been put in place and one of the rules implemented is the restriction of visits to public places and tourist attractions. Therefore, Jakarta Aquarium & Safari is encouraged to innovate in product development and promotions to increase visitor interest so that the number of visits can return to the number before the pandemic began. In this study, the selected attributes are product and promotion. The purpose of this study was to determine (1) the effect of the product on interest in visiting, (2) the effect of promotion on interest in visiting, and (3) the effect of product and promotion on interest in visiting. This study uses convenience sampling techniques. The selected respondents are 164 people who know about Jakarta Aquarium and Safari. Data is analyzed using linear regression method. The results of this study prove that products and promotions affect visit interest either partially or simultaneously.